2008
DOI: 10.1002/chem.200700876
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally Friendly Chemoselective Oxidation of Primary Aliphatic Amines by Using a Biomimetic Electrocatalytic System

Abstract: Environmentally friendly oxidation of primary aliphatic amines to imines has been successfully achieved, under metal-free conditions, by the use of diverse electrogenerated o-azaquinone mediators. High catalytic performance, together with high chemoselectivity, were observed with electron-poor o-azaquinone catalysts generated from 2-aminoresorcinol derivatives. Similar to copper amine oxidase enzymes, these mediators exhibited lower reactivity toward alpha-branched primary amines and no reactivity toward secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(44 citation statements)
references
References 41 publications
3
41
0
Order By: Relevance
“…Of particular note, only the reaction of 4‐methylbenzylamine 2 a with n ‐hexylamine 3 e (Table 2, entry 5) or aminomethylcyclohexane 3 f (Table 2, entry 6) revealed the simultaneous formation of homo‐ and cross‐coupled products ( 4 e or 4 f ) from the outset of the reaction, but with a preference for the homocoupled product 5 . These observations indicated that the homocoupled product was first generated as the sole imine product through the transamination mechanism reported earlier 14. 16 The homocoupled product was further alkylated by the second primary amine R′NH 2 through a transimination process19 to give the cross‐coupled product, the formation of which could be driven by continuous oxidation of the extruded primary amine RCH 2 NH 2 (self‐sorting step) as shown in Scheme .…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…Of particular note, only the reaction of 4‐methylbenzylamine 2 a with n ‐hexylamine 3 e (Table 2, entry 5) or aminomethylcyclohexane 3 f (Table 2, entry 6) revealed the simultaneous formation of homo‐ and cross‐coupled products ( 4 e or 4 f ) from the outset of the reaction, but with a preference for the homocoupled product 5 . These observations indicated that the homocoupled product was first generated as the sole imine product through the transamination mechanism reported earlier 14. 16 The homocoupled product was further alkylated by the second primary amine R′NH 2 through a transimination process19 to give the cross‐coupled product, the formation of which could be driven by continuous oxidation of the extruded primary amine RCH 2 NH 2 (self‐sorting step) as shown in Scheme .…”
Section: Resultsmentioning
confidence: 54%
“…The reaction progressed in all of the solvents used (entries 5–8). But, after 10 h, complete conversion was observed only in MeOH probably because strong solvation of the o ‐iminoquinone 1 ox by MeOH was required to enhance the electrophilicity of its quinonoid moiety, thereby favoring the nucleophilic attack of 4‐methylbenzylamine 2 a 14…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This one-pot procedure commences with the anodic dehydrogenation of a primary amine where an aminophenol is used as the mediator. 529531 Electrochemical oxidation of the mediator furnishes an iminoquinone which can oxidize the amine through condensation and imine isomerization (Figure 34C, right column). The resulting N -aryl-imine can engage another primary amine, giving rise to an N -alkyl-imine.…”
Section: Anodic Oxidationmentioning
confidence: 99%
“…Aliphatic amines are relatively difficult to oxidize as mentioned in the previous studies 51 Along with symmetrical imine formation, the catalyst was also effective for the formation of asymmetrical imines. Depending on the molar ratio and nucleophilic properties of the partner amines, asymmetrical imines can be synthesized efficiently.…”
mentioning
confidence: 95%